Impact of commodity terms-of-trade shocks at disaggregate level - Rebeca Jiménez-Rodríguez; Amalia Morales-Zumaquero (PLoS ONE, 2026)
This paper provides new evidence on the impact of country-specific commodity terms-of-trade shocks on economic growth for developing and emerging countries, not only at aggregate level but also at disaggregate level (agricultural raw materials, food and beverages, energy, and metals). Results suggest: (i) at the country group level, we find evidence supporting the so-called “terms-of-trade disconnect puzzle”; (ii) at the specific country level, the evidence is mixed (i.e., “blessing effect”, “curse effect” or “negligible effect”); (iii) at the commodity category level, it seems that output is mainly affected by shocks to the terms-of-trade for metals, followed to a lesser extent by those for energy; and (iv) statistically significant shocks occur mainly in the short run.